SYARI’AH : ANTARA HUKUM DAN MORAL - Sanusi, Nur Taufik (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2020)
The case of "Mr. Shaw "has generated a long debate about the existence of morals in law. This incident has sparked a long debate about Law and Morals. Law and Moral are two inseparable poles in the study of Islamic law, in contrast to the West which separates the two. According to Coulson, in the view of Islamic society, religious law and morality are often combined in the general philosophy of life. Actually there is a compulsion to obey morals as well as the obligation to carry out the law. But on the other hand, Coulson only pays attention to the lesser role played by the courts in carrying out Islamic (moral) behavior. For courts, there is a difference between legally enforceable regulations and morally desirable ones. The difference between Hanafi formalists and Hanbali moralists can be noted in the matter of legal trickery (Hiyal). According to Coulson Hiyal in this case it is not the same as hiyal which is known in the history of British law where the law is considered to exist from a contrived situation to be used as a procedural basis for the examination at hand, but in Islam, hiyal is truly legal trickery by the overt intention of avoiding the established thing from real law